2017
DOI: 10.1159/000456038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathological Findings of Frontal Fibrosing Alopecia-Associated Lichen Planus Pigmentosus

Abstract: Background: Frontal fibrosing alopecia (FFA) is a primary lymphocytic scarring alopecia occurring mainly in postmenopausal women. A range of facial lesions have been described in FFA, such as lichen planus (LP) pigmentosus, red dots, facial papules, and perifollicular and diffuse erythema. These lesions can be the first sign of FFA. LP pigmentosus is a rare variant of LP. The first description of LP pigmentosus associated with FFA (in 2012) reported 22 cases of LP pigmentosus among 44 cases of FFA affecting So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 12 publications
(17 reference statements)
0
24
0
1
Order By: Relevance
“…We found less sebum content in LP skin compared with normal skin. In lichen planopilaris (Weston and Payette, 2015) and LP pigmentosus (Romiti et al, 2017), the sebaceous glands have been shown to be damaged, and sebaceous glands may be disturbed in classic LP as well.…”
Section: Discussionmentioning
confidence: 99%
“…We found less sebum content in LP skin compared with normal skin. In lichen planopilaris (Weston and Payette, 2015) and LP pigmentosus (Romiti et al, 2017), the sebaceous glands have been shown to be damaged, and sebaceous glands may be disturbed in classic LP as well.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most authors consider FFA as a variant of LPP . This conclusion is supported by their histologic resemblance as well as by reports of patients that associate FFA with bullous lichen planus, lichen planus pigmentosus, 20 nails dystrophy, Graham‐Little‐Piccardi‐Lassueur syndrome and diffuse lichen planopilaris …”
Section: Introductionmentioning
confidence: 84%
“…Their association was first reported by Dlova [31] in 24 Afro-Americans (23 females, 1 male). Later, about 100 cases have been reported worldwide [30,[32][33][34][35][36][37][38][39][40][41][42][43]. Epidemiologic data of the association are conflicting, due to the lack of large case series.…”
Section: Discussionmentioning
confidence: 99%